3D printing of anisotropic Sm–Fe–N nylon bonded permanent magnets. Issue 12 (17th November 2021) - Gandha, Kinjal; Paranthaman, M. P.; Sales, Brian C.; Wang, Haobo; Dalagan, Adrian; Lamichhane, Tej N.; Parker, David S.; Nlebedim, Ikenna C.
Abstract: Fabricating a bonded magnet with a near‐net shape in suitable thermoplastic polymer binders is of paramount importance in the development of cost‐effective energy technologies. In this work, anisotropic Sm2 Fe17 N3 (Sm–Fe–N) bonded magnets are additively printed using SmFeN anisotropic magnetic particles in a polymeric binder polyamide‐12 (PA12). The anisotropic SmFeN bonded magnets are fabricated by Big Area Additive Manufacturing followed by post‐printing alignment in a magnetic field. Optimal post‐alignment results in an enhanced remanence of ∼0.68 T in PA12 reflected in a parallel‐oriented (aligned) measured direction. The maximum energy product achieved for the additively printed anisotropic bonded magnet of Sm–Fe–N in PA12 polymer is 78.8 KJ m −3 . Our results show advanced processing flexibility with 3D printing of the development of SmFeN nylon bonded magnets designed for applications with no critical rare earth magnets. Abstract : This article presents AM fabrication and characterization which includes magnetic properties and mechanical properties of BAAM printed anisotropic Sm–Fe–N based magnets in Nylon (PA12) polymer. Microstructural analysis of AM printed bonded magnet by XRD indicates there is no degradation of Sm–Fe–N main phases after 3D printing. The production of additively printed anisotropic Sm–Fe–N bonded magnets offers the advantage for bonded magnets manufacturing through AM and enables efficient use of rare earth elements thus contributing towards addressing the reduced need of critical materials.